ANALISIS PENGARUH EXPERIENTAL MARKETING TERHADAP LOY-ALITAS PELANGGAN KEDAI PESEN KOPI CABANG JEMBER - Berri, Mohammad Miftahul; Hafidzi, Achmad Hasan; Puspitadewi, Ira (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the Effect of Experiential Marketing on Customer Loyalty of Kedai Pesen Kopi Jember Branch. In this study using quantitative methods, purposive sampling technique involving 100 respondents. The data analysis method used in this research is multiple linear regression analysis. The results of multiple linear regression analysis show that Sense has a positive and significant effect on Customer Loyalty. These findings mean that a good increase will increase customer loyalty at the Jember Coffee Shop. Feel positive and significant effect on Customer Loyalty. These findings mean that a good increase will increase customer loyalty at the Jember Coffee Shop. Think positively and significantly towards Customer Loyalty. These findings mean that a good increase will increase customer loyalty at the Jember Coffee Shop. Act positively and significantly towards Customer Loyalty. These findings mean that a good increase will increase customer loyalty at the Jember Coffee Shop.